Proceedings of the Ninth Annual International Conference on International Computing Education Research 2012
DOI: 10.1145/2361276.2361287
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the disciplinary commons model for high school teachers

Abstract: The Disciplinary Commons (DC) is a model of teacher professional development that encourages members of the group to reflect upon their teaching practices, develop a community, and, more broadly, to become more scholarly about their teaching. The DC involves a series of monthly meetings where university faculty members examine their course in detail while producing a course portfolio. Evaluation of the early DC's suggests that they successfully created a sense of community and sharing among the participants. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…They focus on how best to document and share knowledge within computing classrooms. Ni's doctoral dissertation [15,16,13] focused on creating successful communities of practice for high school computing teachers. She has focused on many of the needs of high school computing teachers (many of the needs are similar to what has been reported by the CSTA), and how best to help them.…”
Section: Communities Of Practicementioning
confidence: 99%
“…They focus on how best to document and share knowledge within computing classrooms. Ni's doctoral dissertation [15,16,13] focused on creating successful communities of practice for high school computing teachers. She has focused on many of the needs of high school computing teachers (many of the needs are similar to what has been reported by the CSTA), and how best to help them.…”
Section: Communities Of Practicementioning
confidence: 99%
“…Goode describes the provision of workshops in computer science and pedagogy and notes that these cause teachers to develop their own small networks of support. Morrison et al [22] adopted the originally university-focused Disciplinary Commons approach [14] to be used with school teachers, by providing monthly meetings to discuss issues of teaching and curriculum over a period of a year. One substantial US study into PD across all subjects suggests that key elements are: having ongoing training that is connected to practice; focusing on specific curriculum content; and building of strong relationships between teachers [10], and this is backed up by similar findings in the UK [9].…”
Section: Professional Development Of Computing Teachersmentioning
confidence: 99%
“…In our work with creating face-to-face communities of teachers, we found that more intensive interactions led to more sharing of recruitment practices. [Morrison et al 2012]. For example, one more intensive recruitment strategy that ICE started was to send out letters to parents of students who did well on a standardized exam.…”
Section: Professional Development Materialsmentioning
confidence: 99%
“…DCCE was aimed at connecting undergraduate and high school computer science teachers in order to develop a community focused on common goals and activities to revitalize undergraduate and high school computing education in Georgia [Morrison et al 2012]. …”
Section: Broad Influence and Impactmentioning
confidence: 99%
See 1 more Smart Citation